Generation Z's Consumptive Crisis and Maqashid Sharia-Based Solutions to the Doom Spending Phenomenon - Misi Anggraini; Duhriah; Hulwati (Islamic Economics and Business Review, 2026)
Abstract This study explores the consumptive crisis among Generation Z and offers solutions based on Maqashid Syariah principles to address doom spending phenomena. Using a qualitative approach, data were collected through literature review and netnographic observation of Generation Z consumption behaviors. Results indicate that excessive consumption driven by emotional triggers and social influences leads to financial instability and psychological stress. The application of Maqashid Syariah emphasizing protection of faith, intellect, progeny, wealth, and life provides a holistic framework for promoting mindful consumption. This research discusses how integrating Islamic ethical values can mitigate impulsive spending and foster sustainable financial habits among youth. The findings contribute to developing culturally relevant strategies for addressing consumer issues in contemporary Muslim societies. Keywords: Generation Z, Doom Spending, Consumptive Crisis, Maqashid Syariah. Islamic Ethics & Mindful Consumption   Abstrak Penelitian ini membahas krisis konsumtif pada Generasi Z serta solusi berbasis prinsip Maqashid Syariah untuk mengatasi fenomena doom spending. Dengan pendekatan kualitatif, data dikumpulkan melalui studi pustaka dan observasi netnografi perilaku konsumsi Generasi Z. Hasil menunjukkan bahwa konsumsi berlebihan yang dipicu oleh faktor emosional dan pengaruh sosial menyebabkan ketidakstabilan keuangan dan stres psikologis. Penerapan Maqashid Syariah yang menitikberatkan perlindungan agama, akal, keturunan, harta, dan jiwa memberikan kerangka holistik untuk mendorong konsumsi yang sadar. Penelitian ini mendiskusikan bagaimana integrasi nilai-nilai etika Islam dapat meredam pengeluaran impulsif dan membangun kebiasaan keuangan berkelanjutan di kalangan generasi muda. Temuan ini berkontribusi pada pengembangan strategi yang relevan secara budaya untuk menangani masalah konsumsi dalam masyarakat Muslim modern. Kata kunci: Generasi Z, Doom Spending, Krisis Konsumtif, Maqashid Syariah, Etika Islam & Konsumsi Sadar